2019
DOI: 10.1016/j.tate.2019.102887
|View full text |Cite|
|
Sign up to set email alerts
|

Practice what you preach: The moderating role of teacher attitudes on the relationship between prejudice reduction and student engagement

Abstract: h i g h l i g h t sUsing multilevel models, we examined the relationship between teachers' prejudice reduction practices and students' engagement. Prejudice reduction practices focused on engaging in dialogue about diversity and confronting intergroup bias. Teachers' explicit multicultural attitudes and implicit attitudes towards ethnic minorities were possible moderators. Prejudice reduction predicted increases in student engagement for teachers with above-average positive explicit attitudes. Our models did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…13.1% of the sample did not specify their ethnic backgrounds. The participants were predominantly female and white, as also found in previously published studies conducted in the Netherlands (e.g., Abacioglu et al, 2019;Van Den Bergh, Denessen, Hornstra, Voeten, & Holland, 2010). Our sample demographics mirror the teaching force in the Netherlands, which has been increasing in diversity, but is still fairly homogenous.…”
Section: Methodssupporting
confidence: 73%
“…13.1% of the sample did not specify their ethnic backgrounds. The participants were predominantly female and white, as also found in previously published studies conducted in the Netherlands (e.g., Abacioglu et al, 2019;Van Den Bergh, Denessen, Hornstra, Voeten, & Holland, 2010). Our sample demographics mirror the teaching force in the Netherlands, which has been increasing in diversity, but is still fairly homogenous.…”
Section: Methodssupporting
confidence: 73%
“…Few studies have controlled for the gender of teachers. The studies present in this review have shown that female teachers have less negative implicit attitudes (Abacioglu et al, 2019;Chin et al, 2020).…”
Section: Teacher's and School's Characteristicsmentioning
confidence: 71%
“…When studies are conducted on experienced teachers, the results are the same, with the presence of implicit negative attitudes toward ethnic minority students (van den Bergh et al, 2010;Vezzali et al, 2012;Conaway and Bethune, 2015;Kumar et al, 2015;Glock and Böhmer, 2018;Harrison and Lakin, 2018a;Kleen and Glock, 2018;Chin et al, 2020). Just one study found a positive implicit attitude toward ethnic majority students but not a negative one toward ethnic minority students (Abacioglu et al, 2019).…”
Section: Teaching Statusmentioning
confidence: 95%
See 1 more Smart Citation
“…Further, other studies have provided evidence that supports the link between teachers’ attitudes towards inclusive education and/or their self‐efficacy beliefs with their use of inclusive teaching practices (e.g., Bosse et al, 2016; De Neve, Devos, and Tuytens, 2015; Holzberger, Philipp, and Kunter, 2013; Knauder and Koschmieder, 2019; Schüle, Schriek, Besa, and Arnold, 2016; Sharma and Sokal, 2016). In a recent study by Abacioglu et al (2019), it was revealed that teachers’ multicultural attitudes are linked with reduction in prejudice.…”
Section: Introductionmentioning
confidence: 98%